Pengembangan Media Pembelajaran PERMUTASI (Permainan Ular Tangga Berbasis Materi) Matematika SMP Kelas VIII - Bryan Pudji Hartono; Bayu Bagus Riyandiarto (UNION : Jurnal Ilmiah Pendidikan Matematika, 2021)
Innovative learning media is needed in order to attract students in learning mathematics. The purpose of this research was to develop and to know its feasibility a learning media of snakes and ladder games based on mathematical materials. The method was Research and Development (R&D). The development was carried out using a 4-D development model. After conducting teacher, student and literature analysis, researchers performed product which then reviewed and validated by material and evaluation experts. The results of product design assessments by experts has been qualified in the "excellent" criteria. After revised, design was produced and then given to the teacher to be tested to the students. The results of product assessments by teachers and students also stated that the product included in the "excellent" criteria. Based on that assessments, the product has been qualified in the "excellent" criteria which means that this product are deserves to be used as an innovation for further math learning.